Seasonal Change and Spatial Distribution of Traffic Noise in Seferihisar, Turkey - SAY, Nuriye; ÖKTEN, Sinem Özyurt; AYSU, Asuman; YALÇINKAYA, Nermin Merve (Archives of Acoustics, 2017)
In this study, traffic noise in Seferihisar, which is a holiday resort by the Aegean Sea in the West of Turkey, was investigated. The noise occurring in summer and winter, on weekdays, and at weekends was mapped separately. Besides, land uses exposed to traffic noise were specified. In the carried out method, the land uses were primarily mapped by using the satellite images of the study area. Then, the noise was measured at 46 points during ten days in summer and winter, on weekdays and at weekends, and it was mapped by using Inverse Distance Weighting (IDW) method and by means of Geographic Information System (GIS) techniques. The measurements were taken in the daytime (07:00–19:00), in the evening (19:00–23:00), and at night (23:00–07:00) as stated in the Turkish Regulation of Assessment and Management of Environmental Noise. Since the time interval of the daytime measurements was large, the noise was measured in three different periods for the daytime measurements. In the formation of noise maps, logarithmic averages of all measurements taken at each point were used. The noise maps were overlapped with the land use maps by the help of the GIS techniques; the land use affected by the noise was analyzed. The results showed that the road traffic noise varied from summer to winter seasons in the study area depending on heavy or light traffic. The noise occurring in summer showed an increase both on weekdays and at weekends. While the limit value was exceeded in 49 of the measurement averages taken in winter, the limit value was exceeded in 96 measurements taken in summer. The noise maps formed according to the IDW method displayed that the areas in which the limit value was exceeded in the daytime in summer took up 14.27% of the study area while this rate went down to 4.06% in winter. The study area is one of the most important destinations for summer holiday. 20.12% of the area that exceeded the limit value in summer was builtup and 10.69% of them was tourism area. The noise together with population and traffic that increase in summer season is an important environmental problem against which some precautions should be taken. The findings of the study present significant results which might guide local governments in preventing and managing the noise.